An institutional experience: A retrospective analysis of the effect of transitioning from follicular lesion of undetermined significance to atypia of undetermined significance with subclassified atypia on interobserver concordance, rates of neoplasia, and rates of malignancy. Issue 1 (16th September 2020) - Kroll‐Wheeler, Lauren; Cantley, Richard; Pang, Judy C.; Soles, Brian S.; Smola, Brian; Jing, Xin; Lew, Madelyn
Abstract: Introduction: The rate of malignancy (ROM) in thyroid fine needle aspirations (FNA) classified under "atypia of undetermined significance (AUS)/follicular lesion of undetermined significance (FLUS), including Hürthle cell type (HLUS)" category of The Bethesda system for reporting thyroid cytopathology (TBSRTC) in literature is highly variable. The 2018 TBSRTC was updated to note a preferred categorization of AUS cases into subcategories. This study evaluates the impact of AUS subclassification on rates of neoplasia (RON), rates of malignancy (ROM), and cytopathologist (CP) concordance. Methods: 93 thyroid FNAs previously diagnosed as FLUS or HLUS from January 1, 2013 to December 31, 2014 with subsequent surgical resection were identified. Four CPs reclassified these cases using TBSRTC AUS subcategories of follicular cells with architectural and/or cytologic atypia, predominantly Hürthle cells, and atypical lymphocytes. RON and ROM were calculated for each diagnostic subcategory for each CP. Results: The original RON and ROM for FLUS cases were 31.4% and 15.1% and were 77.8% and 22.2% for HLUS cases. 10.8% of cases showed diagnostic concordance amongst the four CPs. The most frequently utilized subcategory was architectural atypia. RON ranges for architectural atypia, cytologic atypia, architectural and cytologic atypia, and predominantly Hürthle cells were 28.1% to 35.7%, 0% to 33.3%, 35.3% to 66.7%, and 57.1% to 87.5%. The range of ROM was 13.9% to 16.7%, 0% to 33%, 0% to 42.9%, and 0% to 25%, respectively. Conclusion: RON for AUS predominantly Hürthle cells subcategory was higher than previously reported, which may indicate use for tailored patient management pathways. AUS subclassification can result in significant interobserver variability. Therefore, institutions may consider consensus/quality control sessions to optimize diagnostic concordance.